Fournier gangrene – would you KISS it? - Matias, Miguel João Ribeiro; Guimarães, Diogo; Vilela, Manuel; Sousa, Juliana; Bexiga, Joaquim (GMS Interdisciplinary Plastic and Reconstructive Surgery DGPW, 2023)
Fournier gangrene is a disease characterized by necrotizing fasciitis of the perineal and genital region, resulting from synergistic polymicrobitic infection. Most infections can be localized to a cutaneous, urethral, or rectal source and can culminate in a fulminant sepsis. Current state of the art is systemic broad-spectrum antibiotics and serial aggressive debridement which result in superficial perineal defect of wide dimensions.We compiled all the cases of Fournier gangrene that required reconstruction after debridement in Centro Hospitalar Universitário Lisboa Central from 2018 to 2022. Inclusion criteria were reconstruction for Fournier defects and patients’ age 18 to 90 years old. Exclusion criteria were patients who didn’t require reconstruction or didn’t complete it due to death or transfer to another healthcare institution. Reconstructive procedures and complication rates are reported as whole numbers and percentages of total.The initial search yielded 32 patients. There were 2 (6.2%) patients with defects that healed by secondary intention, 6 (18.7%) with delayed primary closure, 4 (12.5%) with implantation of the testicle in a medial thigh pocket, 12 (37.5%) with skin grafts, 4 (12.5%) with scrotal advancement flaps, 2 (6.2%) with flaps, and 2 (6.2%) with flaps and skin grafts in combination. Four outcomes were evaluated: number of patients, defect size, method of reconstruction, and wound-healing complications.Most reconstructive techniques provide reliable coverage and protection of testicular function with an acceptable cosmetic result. The reconstructive options need to be patient tailored in order to achieve long lasting results with a minimum of postoperative morbidity.